Persepsi citra merek dan komunikasi interpersonal sebagai prediktor kepuasan konsumen: Studi pada mahasiswa pengguna e-Wallet OVO - Endang Prastuti; Winda Sari (University of Muhammadiyah Malang, 2022)
This study aims to determine the effect of brand image perception and interpersonal communication on consumer satisfaction either partially or simultaneously. This research design uses quantitative correlational research. The research instrument used is the Brand Image Perception Scale, Interpersonal Communication Scale, and Consumer Satisfaction Scale. There were 122 subjects involved in this study obtained using the accidental sampling technique. The data obtained were then analyzed using multiple regression analysis techniques. This means that simultaneously the two variables can predict high and low consumer satisfaction. This study indicates a positive influence between perceived brand image and interpersonal communication on consumer satisfaction in students using OVO E-wallet at the State University of Malang (p < 0.005; R Square 0.357).